2020
DOI: 10.1016/j.dib.2020.106228
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic data on the composition of bacterial communities in lake environment sediments for fish farming by next generation Illumina sequencing

Abstract: This article contains data on the bacterial communities of lagoon sediments with fish potential in the Central Andes of Peru. The surface sediment samples were collected from four lagoons destined for continental water fish farming. DNA extraction was performed from 0.5 g of sample through the Presto™ Soil DNA Extraction Kit. Bacterial sequencing of the 16S rRNA amplicon was performed on the DNA extracted from the sediment. At least 36 Phyla bacteria were detected, the bacterial communities being dominated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The FASTQ files generated by the program FASTQC v0.11.9 were processed to know the length of the readings, the quality of the bases and the percentage of nucleotide bases, as we showed in a preliminary study in lake sediment bacterial communities 63 . Subsequently, quality filtering and removal of regions of the primer and adapters present in the readings was performed using the Trimmomatic v0.39 program 64 with minimum trimming values of Q30 and trimming of readings below 30 bp.…”
Section: Methodsmentioning
confidence: 99%
“…The FASTQ files generated by the program FASTQC v0.11.9 were processed to know the length of the readings, the quality of the bases and the percentage of nucleotide bases, as we showed in a preliminary study in lake sediment bacterial communities 63 . Subsequently, quality filtering and removal of regions of the primer and adapters present in the readings was performed using the Trimmomatic v0.39 program 64 with minimum trimming values of Q30 and trimming of readings below 30 bp.…”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al (2015) found that environmental factors influenced the distribution of ammonifying and denitrifying bacteria in the lakes of China. Custodio et al (2020) suggested that the bacterial communities in lake environments experienced stress from fish farming in the Peruvian Andes. Microorganisms usually sink into the sediment of aquaculture water and eventually become a source of nutrients for aquatic organisms (Shaughnessy et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Custodio et al . (2020) suggested that the bacterial communities in lake environments experienced stress from fish farming in the Peruvian Andes. Microorganisms usually sink into the sediment of aquaculture water and eventually become a source of nutrients for aquatic organisms (Shaughnessy et al .…”
Section: Introductionmentioning
confidence: 99%